Using Old Solutions to New Problems Natural Drug Discovery in the 21st Century - Kulka, Marianna (IntechOpen, 2013)
The medicinal use of plants, animals and microorganisms has been a part of human evolution and likely began before recorded history. Is it possible that this knowledge can be used to create powerful new drugs and solve some of the human health problems facing us today? This book is a collection of an expert team of agronomists, chemists, biologists and policy makers who discuss some of the processes involved in developing a naturally-sourced bioactive compound into a drug therapy. These experts define a natural compound and elucidate the processes required to find, extract and define a naturally-derived bioactive molecule. Finally, they describe the necessity for understanding the fundamental mechanisms of disease before applying bioactive molecules in bioassay-guided drug discovery platforms.